A case of pure red cell aplasia during nivolumab therapy for cardiac metastatic melanoma. Issue 6 (December 2017) - Yuki, Akihiko; Takenouchi, Tatsuya; Takatsuka, Sumiko; Ishiguro, Takuro
Abstract : Nivolumab is an antibody against programmed cell death 1 and functions as an immune checkpoint inhibitor for various malignancies, including unresectable melanomas. Nivolumab causes several immune-related adverse events, which typically include skin rash, pneumonitis, thyroid dysfunction, hepatitis, and colitis; in rare cases, anemia may be present. There are several reports of autoimmune hemolytic anemia that has developed in response to nivolumab; however, there are few reports of pure red cell aplasia (PRCA). We describe a patient who developed PRCA during nivolumab administration. A 70-year-old Japanese woman received nivolumab for cardiac metastasis from malignant melanoma from an unknown site. Twenty-one months after nivolumab administration (31 courses), treatment was discontinued because she developed severe anemia. Blood test results indicated normocytic, normochromic anemia, and reticulocytopenia, but all other components were normal. Bone marrow aspiration showed increased megakaryocytes and decreased erythroblasts; these findings were consistent with PRCA. Anemia improved without recurrence after treatment with corticosteroids and blood transfusions. The steroid dosage was reduced gradually, and to date, the patient has not experienced recurrence of anemia. The tumor decreased in size and the patient has shown a continued response to treatment with decrease in disease for 3 years. Although it is unclear how nivolumab causes PRCA, hematological toxicities have been reported in patients treated with immunotherapy drugs. PRCA might be an unrecognized immune-mediated adverse event that did not manifest during the clinical trial phase.